Exploración de la interdisciplinariedad en un caso de planificación curricular de experiencia de aprendizaje (EDA) del nivel secundaria (Revista Peruana de Investigación Educativa, 2025)
Because of the pandemic of COVID-19, interdisciplinarity in the Peruvian curriculum was emphasized through the design of learning experiences (EDA in Spanish). This type of curricular planning generates some disagreement in teachers. For this reason, the present work shows an approach to the interdisciplinarity features of curricular design planned in the EDA, from a case selected of several curricular documents published and shared by social networks in 2022. Through the document analysis, it was observed in the selected case some traces of interdisciplinarity work. However, the curricular planning would not prioritize an aimed specific topic, but highlight some aspects of each curricular subject in an isolated manner. In this way, it is necessary more studies on associated and direct factors that would have generated these features in the curricular planning.